2022
DOI: 10.1017/s1355617722000595
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal change in serial position scores in older adults with entorhinal and hippocampal neuropathologies

Abstract: Objective: Serial position scores on verbal memory tests are sensitive to early Alzheimer’s disease (AD)-related neuropathological changes that occur in the entorhinal cortex and hippocampus. The current study examines longitudinal change in serial position scores as markers of subtle cognitive decline in older adults who may be in preclinical or at-risk states for AD. Methods: This study uses longitudinal data from the Religious Orders Study and the Rush Memory and Aging Project. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Later, after a delay of several minutes, participants are asked to recall as many words from the initial list as possible in any order, providing a total delayed recall score. Following Gicas et al 23,24 we defined immediate primacy as the ability to recall the first three words presented in the first three trials (i.e., A1-A3, B1-B3, and C1-C3), immediately after presentation of that list, and then divided that sum by the total number of possible items (i.e., nine). For comparison, we also computed an alternative measure of immediate primacy which included only the first three words presented in the first trial (i.e., A1-A3; one list immediate primacy).…”
Section: Cognitive Assessmentmentioning
confidence: 99%
See 4 more Smart Citations
“…Later, after a delay of several minutes, participants are asked to recall as many words from the initial list as possible in any order, providing a total delayed recall score. Following Gicas et al 23,24 we defined immediate primacy as the ability to recall the first three words presented in the first three trials (i.e., A1-A3, B1-B3, and C1-C3), immediately after presentation of that list, and then divided that sum by the total number of possible items (i.e., nine). For comparison, we also computed an alternative measure of immediate primacy which included only the first three words presented in the first trial (i.e., A1-A3; one list immediate primacy).…”
Section: Cognitive Assessmentmentioning
confidence: 99%
“…Gicas et al, 23 for example, have shown that higher immediate primacy performance is associated with less risk of AD neuropathology, including hippocampal sclerosis; and increased pathology predicted greater longitudinal decline in primacy performance. 24 Gicas et al 23,24 the words in any order (immediate recall). Subsequently, they are also asked to free recall the words after a delay (delayed recall).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations